Changing World, Transforming God's Word: Narrative, Ecological and Future-Oriented Approaches to Scriptures - Ibita, Maricel S. (Concilium, 2022)
In a world characterized by post-global economics, post-national migration, post-human climate crisis, post-truth politics, and the COVID-19 pandemic, how do we read God's Word? I suggest that newer biblical interpretation methodologies that are contextual, inclusive, integrated, and transformational are needed today. Examples of these are narrative criticism, ecological hermeneutics, and the normativity of the future approach. Basic ecclesial communities and theologians may use these methodologies alone or in combination with each other to recontextualize God's Word and help build a better post-pandemic future. Micah 4:1-5 in dialogue with the United Nations Sustainable Development Goals serve as a brief test case.